Characterization of winged helix domain fusion endonucleases as N6-methyladenine-dependent type IV restriction systems - Helbrecht, Igor; Heiter, Daniel; Yang, Weiwei; Vincze, Tamas; Hanneman, Andrew; Lutz, Thomas; Ettwiller, Laurence; Bochtler, Matthias; Xu, Shuang-yong (Frontiers in Microbiology, 2024)
Winged helix (wH) domains, also termed winged helix-turn-helix (wHTH) domains, are widespread in all kingdoms of life, and have diverse roles. In the context of DNA binding and DNA modification sensing, some eukaryotic wH domains are known as sensors of non-methylated CpG. In contrast, the prokaryotic wH domains in DpnI and HhiV4I act as sensors of adenine methylation in 6mApT (N6-methyladenine, 6mA or N6mA) context. DNA binding modes and interactions with the probed dinucleotide are vastly different in the two cases. Here, we show that the role of the wH domain as a sensor of adenine methylation is widespread in prokaryotes. We present previously uncharacterized examples of PD-(D/E)XK—wH (FcyTI, Psp4BI), PUA—wH—HNH (HtuIII), wH—GIY-YIG (Ahi29725I, Apa233I) and PLD—wH (Aba4572I, CbaI) fusion endonucleases that sense adenine methylation in the Dam+ G6mATC sequence contexts. Representatives of the wH domain endonuclease fusion families with the exception of the PLD—wH family could be purified, and an in vitro preference for adenine methylation in the Dam context could be demonstrated. Like most other modification-dependent restriction endonucleases (MDREs, also called Type IV restriction systems), the new fusion endonucleases except those in the PD-(D/E)XK—wH family cleave close to, but outside the recognition sequence. Taken together, our data illustrate the widespread combinatorial use of prokaryotic wH domains as adenine methylation readers. Other potential 6mA sensors in modified DNA are also discussed.